The effect of stopping water exercise for 12 weeks on the functional fitness of elderly women Efeito do período de interrupção de atividades aquáticas na aptidão funcional de idosas - da Rosa M.F.* (2008)
The objective of this study was to investigate the effect of a 12-week pause in exercising in water on the functional fitness of elderly women. The sample was 31 elderly women, with x = 68.97 years (SD = 5.34), all participants in a water exercise program. The women were tested in November 2005 and, after a 12-week pause in water exercises, in March 2006, using the American Alliance for Health, Physical Education, Recreation and Dance - AAHPERD test battery. The statistical analysis was descriptive, using simple frequencies and percentages, plus the t test for paired samples. A statistically significant difference was observed between mean scores for coordination, agility and the general functional fitness index (GFFI) at the end of the exercise program and 12 weeks later. The GFFIand coordination scores had reduced after the 12- week period, but the participants' agility had improved. It was concluded that a 12-week pause in water exercise impacted the GFFIof these elderly women. These results emphasize the importance of physical exercise during the ageing process and of raising awareness of the need for the elderly to keep physically active even during the holiday period in order to improve and/or maintain functional fitness levels.